Fast distribution network reconfiguration algorithm based on minus feasibility analysis unit - He, Yuqing; Lu, Pingjiang; Deng, Lujiu; Yin, Jianguo; He, Yuanyuan; Zhang, Zhenghua; He, Hongbin (The Journal of supercomputing, 2020)
Because of the defects of the nonlinear optimization algorithm and the complexity of the physical constraints of the distribution network reconfiguration, the speed and the convergence of the algorithms are usually poor. A fast algorithm for distribution network reconfiguration based on feasibility analysis unit is presented. Firstly, the network simplification method is presented based on the radial construction of the distribution network, and then the conception of basic loop is proved by using the impedance-branch dissipation power theory. By analyzing the quantitative relationship between load and branch power loss and the characteristics of the nodal impedance matrix, the basic loop that is just the minus feasibility analysis unit of the physical reconfiguration optimization is verified. Based on this theory, the path dissipation factor is presented which formed a novel heuristic rules and an improved branch exchange method in order to solve the distribution network reconfiguration problem. In this proposed method, the processing sequence of all the basic loops is firstly defined by the load dissipation component, and then optimal reconfiguration scheme is simply obtained by repeating the above operation until there is no branch need to exchange. Test results of IEEE-69 buses system verified the efficiency and reliably of the proposed method.